(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This scientific article analyzes the strategic changes in the tax policy of the Republic of Uzbekistan, the optimization of tax rates, and the issues of digitalization of tax administration. Particular attention is paid to the comparative analysis of Uzbekistan’s tax practices with international experience (WTO requirements and models of developed countries). At the end of the article, scientific and practical recommendations for further improvement of the system are presented.